Puerperal Sepsis among Reproductive Age Women: A Review - Basemah Ali Alabdullah et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Puerperal sepsis, a bacterial infection that affects women in the postpartum period, is a leading cause of maternal morbidity and mortality globally, particularly in low- and middle-income countries. This review examines the associated risk factors for puerperal sepsis in reproductive-age women, including hygiene and sanitation issues, prolonged labor, cesarean sections, underlying maternal health conditions, and limited access to healthcare. Furthermore, strategies for prevention, such as improving sanitation, promoting facility-based deliveries, and enhancing postpartum care, are discussed. This review aims to highlight the critical need for effective interventions to reduce the incidence of puerperal sepsis and improve maternal health outcomes. Keywords: Puerperal Sepsis, Reproductive Age Women. Received Date: September 14, 2024 Accepted Date: October 12, 2024 Published Date: November 13, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/226